Художній текстиль як складова національно-культурного простору (про Першу та Другу всеукраїнські трієнале художнього текстилю) - Чегусова, З.; Печенюк, Т. (Студії мистецтвознавчі, 2009)
The article is dedicated to the issue of the development of the modern art textile on the base of expositions of the First and Second Ukrainian Triennials of Art Textile of the Commonwealth of Artists in Kyiv, 2004, 2007. The authors focused on the modern tendencies of development of the art textile, which is going through complicated transformations of images in the late 20th and early 21st centuries. The authors also focus on the issues of innovative styles and experiments formation in the sphere of technologies and materials as well as they characterize the works of various styles – from the traditional to the conceptual ones, which include figurativeness and abstraction. Special focus was made on the traditional types of the Ukrainian art textile (handwork tapestry, carpet, batic, wollen carpet) and the innovative ones (collage, installation). The works of various creative personalities were analyzed, notably the works of leading craftsmen of non-traditional needle (modern embroidery) and glue techniques. The authors confirm that the Ukrainian art textile, which became a national phenomenon at the beginning of the 21 century, develops according to the modern art ideas and belongs to Postmodernism and New Avantgardism together with other kinds of art. The works of the Ukrainian artists are supposed to be recognized at the international exhibitions and workshops.